2005
DOI: 10.1002/art.21084
|View full text |Cite
|
Sign up to set email alerts
|

The health assessment questionnaire disability index and scleroderma health assessment questionnaire in scleroderma trials: An evaluation of their measurement properties

Abstract: Objective. To evaluate the measurement properties of the Health Assessment Questionnaire (HAQ) disability index (DI) for group comparisons in scleroderma trials, and to determine if the Scleroderma Health Assessment Questionnaire (SHAQ) visual analog scales confer any measurement advantage over the HAQ DI. Methods. A computer search for articles describing the use of the HAQ DI and SHAQ in scleroderma was performed. Evidence supporting the sensibility, reliability, validity, and responsiveness of these measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 36 publications
(42 reference statements)
1
67
0
Order By: Relevance
“…They also reported excellent face validity and acceptable time to completion. These findings are comparable to other commonly used questionnaires, such as the Health Assessment Questionnaire [36]. The recommended standard of feasibility suggests that self-reported instruments should be completed in less than 15 minutes [37].…”
Section: Discussionsupporting
confidence: 78%
“…They also reported excellent face validity and acceptable time to completion. These findings are comparable to other commonly used questionnaires, such as the Health Assessment Questionnaire [36]. The recommended standard of feasibility suggests that self-reported instruments should be completed in less than 15 minutes [37].…”
Section: Discussionsupporting
confidence: 78%
“…However, there are several instruments that address similar conceptual constructs to the SSPRO (other than the PE construct) and have also been validated in SSc: CHFS,30 HAQ-DI,31 SF-3632 and PROMIS-29 33. To compare, the SSPRO PL subscale had moderate-to-strong correlations with the CHFS (0.73) and HAQ-DI (0.60).…”
Section: Discussionmentioning
confidence: 99%
“…7,14,15 In the study by Steen et al, 9 who created SHAQ, and 10 The addition of these five VASs addressing the symptoms of systemic scleroderma makes SHAQ a specific questionnaire that assesses function in patients with this disease. 18 The VAS relating to Raynaud's phenomenon was not validated in the original questionnaire, but was administered in the study by Georges et al 10 in order to validate the French version of SHAQ.…”
Section: External Validitymentioning
confidence: 99%
“…18 This author reported that both questionnaires were sensitive for assessing difficulties in performing activities of daily living, among patients with systemic scleroderma, and that SHAQ enhances HAQ, since it assesses the impact of the symptoms of the disease on daily activities.…”
Section: External Validitymentioning
confidence: 99%